2017
DOI: 10.1111/cge.12902
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism for a SLC2A1 mutation: implications for genetic counseling for GLUT1 deficiency syndrome

Abstract: A heterozygous SLC2A1 mutation in the severely affected child was inherited from his less severely affected mother who was mosaic for the mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Trio test identified cases with parental mosaicism. Parental mosaicism of SLC2A1 has been reported (20,21), and the level of mosaicism appears to be related to symptoms, which is consistent with the results of this study. Parental mosaicisms of SPTAN1 and RORA have not been reported yet to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Trio test identified cases with parental mosaicism. Parental mosaicism of SLC2A1 has been reported (20,21), and the level of mosaicism appears to be related to symptoms, which is consistent with the results of this study. Parental mosaicisms of SPTAN1 and RORA have not been reported yet to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Postzygotic mosaicism describes individuals who developed from a single zygote but consist of multiple cell populations with different genotypes (Strachan and Read 1999). The mosaicism arises due to postzygotic errors in DNA replication (De 2011;Lupski 2013) and can lead to disease states in the mosaic carriers (Poduri et al 2013;Priest et al 2016;Terracciano et al 2016), or in the heterozygous offspring inheriting the mutant allele (Dal et al 2014;Huang et al 2014;Acuna-Hidalgo et al 2015;Dou et al 2017), and contribute to the recurrent risk of genetic disorders in children (Depienne et al 2010;Xu et al 2015;Takahashi et al 2017). With the recent development of deep sequencing technology, a small number of studies reported the genomic pattern of postzygotic single-nucleotide mosaicisms (pSNMs) in noncancerous human samples (Huang et al 2014(Huang et al , 2018Dou et al 2017;Ju et al 2017), and this has enabled the quantitative analysis of pSNMs during the normal developmental process.…”
mentioning
confidence: 99%
“…The first group of mechanisms that comes to mind that may underlie phenotypic variability in IEM is a difference in the expression of the abnormal protein, often determined by genetic factors. Likewise, phenotypic severity and age of onset are expected to be modulated by differences in residual protein activity driven by (i) random X inactivation such as in ornithine transcarbamylase (OTC) deficiency, pyruvate dehydrogenase (PDH) deficiency, adrenomyeloneuropathy (AMN) or Fabry disease; (ii) genetic imprinting like in Niemann-Pick type A/B disease (Simonaro et al 2006) or citrullinemia (Verma et al 2017); (iii) somatic mosaicism like in OTC deficiency (Giorgi et al 2000), PDH deficiency (Ridout et al (Takahashi et al 2017); (iv) composite heterozygosity between a pathogenic mutation and a modifier variant either in the same gene, as in maple syrup urine disease (MSUD) (Frézal et al 1985), or in a different gene, as in fatty acid oxidation defect (Vockley et al 2000)o rO T Cd e f i c i e n c y (Mira and Boles 2012)-the so-called synergistic heterozygosity; (v) mutational load (i.e., heteroplasmy) in mitochondrial DNA diseases like NARP/Leigh or MELAS syndromes; and (vi) functional consequences of the mutation that may lead to a conformational versus a metabolic defect like in triose phosphate isomerase deficiency (Orosz et al 2009).…”
mentioning
confidence: 99%